Tooth fragment embedded in the upper lip after dental trauma: A case report presenting an immediate diagnostic approach and complete rehabilitation - A Agarwal; U Rehani; V Rana; N Gambhir (Wolters Kluwer Medknow Publications, 2013)
Dental traumas are reasonably common, especially in children and adolescents. They are caused by many factors with fall accounting for the most frequent one. Dental trauma requires a special consideration when dental fractures accompany soft tissue lacerations. Dental fragments occasionally penetrate into soft tissue and may cause severe complications. Early diagnosis and surgical removal of these fragments could prevent undesirable foreign body reaction and scarring. This report presents immediate diagnosis and management of a case in which dental fragment was embedded in the lip soft tissue.